2005
DOI: 10.1080/01650250444000306
|View full text |Cite
|
Sign up to set email alerts
|

Korean mothers’ proactive socialisation beliefs regarding preschoolers’ social skills

Abstract: The purpose of the present study was to examine the proactive socialisation beliefs (goals, attributions, strategies) of Korean mothers regarding preschoolers’ social skills (sharing, controlling negative emotions, and helping others). Participants were 116 mothers in Seoul, Korea. The reasons that mothers provided for the importance of each skill, their causal attributions for the acquisition of those skills, and the socialisation strategies that would be most effective, were targeted. Korean mothers rated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 42 publications
1
41
0
2
Order By: Relevance
“…Interestingly, mothers in our study reported an average score of proactive sensitivity as .49 (0 = reactive sensitivity only; 1 = proactive sensitivity only), which suggests that they may be using both proactive and reactive sensitivity to similar degrees. This may be due to the interplay between traditional collectivistic values and individualistic values in contemporary Korean society (Park & Cheah, 2005). Supporting the hypothesis, however, Korean mothers' higher proactive sensitivity (i.e., responding to anticipated needs of the child), rather than higher reactive sensitivity (i.e., responding to expressed needs when requested by the child), was associated with children's effective regulation of emotion.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Interestingly, mothers in our study reported an average score of proactive sensitivity as .49 (0 = reactive sensitivity only; 1 = proactive sensitivity only), which suggests that they may be using both proactive and reactive sensitivity to similar degrees. This may be due to the interplay between traditional collectivistic values and individualistic values in contemporary Korean society (Park & Cheah, 2005). Supporting the hypothesis, however, Korean mothers' higher proactive sensitivity (i.e., responding to anticipated needs of the child), rather than higher reactive sensitivity (i.e., responding to expressed needs when requested by the child), was associated with children's effective regulation of emotion.…”
Section: Discussionmentioning
confidence: 54%
“…Parents' gender-specific emotion socialization goals and practices are also apparent in contemporary Korean society (Park & Cheah, 2005). Few Korean studies, however, explored gender differences in the association between parenting practices and child social emotional outcomes, and the results are inconsistent (e.g., Kwon & Lee, 2005;Oh, 2014).…”
Section: Gender-specific Emotion Socializationmentioning
confidence: 99%
“…Two nations represented cultural values that emphasize interdependence (India and Nepal; Mishra, in press), two nations represented cultural values that emphasize independence (Germany and the USA), and one nation represented a tradition of valuing interdependence which may come into conflict with its rapid modernization (South Korea; Park & Cheah, 2005;Chang, 2010). We do not assume cultural homogeneity within each nation; the cross-cultural design allowed us to optimize variance in mothers' intuitive theories in order to examine both similarities and differences between and within cultural groups.…”
Section: Methodsmentioning
confidence: 99%
“…Elias (1997) assures that academic and professional successes can't be achieved without the individual acquiring the social skills. Other studies pin pointed that the parents' behaviour and trends are important factors in acquiring the social skills by the students (Park & Cheah, 2005), and that lack of social skills is correlated with noticeable difficulties in the students, which are related with their future behaviours and emotional development. Also, social skills result in the students giving more attention to their educational tasks and reduce behavioural problems, while insufficient social skills prophesizes great difficulties in the future life of individuals, also, social skills are correlated with better intellectual processing (Al-Elwan, 2011).…”
Section: Introductionmentioning
confidence: 99%